Does teacher-student relationship mediate the relation between student misbehavior and teacher psychological well-being? - Mohamad Arief Rafsanjani; Heni Purwa Pamungkas; Etika Dhewi Rahmawati (Universitas Negeri Malang, 2019)
One dominant determinant of teacher psychological well-being is the problem of student discipline. This study seeks to describe how the process of student disciplin (seen of student misbehavior) may affect teacher psychological well-being (seen of enthusiasm and emotional exhaustion) by including a mediator variable, namely teacher-student relation. This study was conducted on 159 economics teachers of senior high schools in Malang (Malang City and Malang Regency) using a total population sampling. We used structural equation modeling (SEM) for data analysis, followed by a sobel test the mediating role of variable in teacher-student relationship. The results showed that student misbehavior had a negative effect on work enthusiasm but a positive effect on students' emotional exhaustion. This study also found that teacher-student relation mediate the relationship between student misbehavior and teacher psychological well-being. The results of this study explain the process of student misbehavior in establishing teacher-student relations which ultimately influences teacher work enthusiasm and emotional well-being.